Driving Brand Loyalty in Creative Culinary Industry - Butar Butar, Ivan Destian; Pratama, Mohammad Harry; Pangaribuan, Christian Haposan (Universitas Pelita Harapan, 2021)
The government has emphasized the increasing number of the creative culinary industry in Indonesia to increase support in this area. One of the flourishing brands running a creative culinary business in Indonesia is Warunk Upnormal. The growth of the player in this industry has grown some concern about such business's sustainability since the related industry has low entry barriers. This research aims to know how well the known drivers of brand loyalty, including variables brand awareness, perceived quality, brand image, perceived value, pleasure, and customer satisfaction, affect brand loyalty in Warunk Upnormal. This research used a quantitative method in finding the relationships among variables and used primary data to be processed. The design and development of the questionnaire are based on the pretested model and distributed toward 208 respondents. The overall result of this research shows that perceived quality affects most toward pleasure, followed by perceived value, then brand awareness. This research also shows the positive and significant relationship of pleasure toward customer satisfaction and customer satisfaction toward brand loyalty.